Gender and Motivation among EFL Students - Firdani Firdani; Nanda Marlina Abdul Samad; Siti Sarah Fitriani; Iskandar Abdul Samad; Rizki Ananda (Universitas Teuku Umar, 2019)
Motivation is an important factor for explaining the success or failure of any complex task. Motivation is related to gender which plays an important role in one’s life. This study focuses on finding out the correlation between gender and motivation among students in learning English as a foreign language. It looks particularly on determining how motivation in learning English as a foreign language is influenced by gender. The researchers employed qualitative research where the data were obtained by questionnaire. Ten participants of this research were chosen for this research. They are five males and five female postgraduate students of English Education Department of Syiah Kuala University. This research found that there is significant correlation between gender and motivation among EFL students in learning English in which female students tend to be more successful and motivated than the male students regarding learning English.